Another cause of difficult airway in an elderly patient: Tongue‐base abscess. (7th May 2018) - Binar, Murat; Arslan, Fatih; Aydin, Umit
Abstract : Objective: An abscess of the tongue base is rare, but it can be a potentially life‐threatening situation in elderly patients. Case report: A 72‐year‐old male patient presented with mid‐anterior neck swelling, odynophagia, poor oral hygiene and severe dyspnoea. After a difficult intubation, the muscles were dissected via a submental suprahyoid approach and the abscess was drained. Conclusion: Poor oral hygiene may predispose elderly patients to tongue‐base abscesses. An early decision should be made for surgical drainage due to the risk of airway obstruction.